Techinques and algorithmic advances in the SKA era. Issue Volume 14:Issue A30(2018) (August 2018) - Vacca, V.; Govoni, F.; Murgia, M.; Enßlin, T.; Oppermann, N.; Feretti, L.; Giovannini, G.; Jasche, J.; Junklewitz, H.; Loi, F.
Abstract: The new generation of radio interferometers will deliver an unprecedented amount of deep and high resolution observations. In this proceedings, we present recent algorithmic advances in the context of the study of cosmic magnetism in order to extract all the information contained in these data.